PENGARUH ANGGARAN BERBASIS KINERJA DAN GOOD GOVERNANCE TERHADAP KINERJA VALUE FOR MONEY (Survei Pada Pemerintah Daerah Kota Palu) - Fajarningtyas, Liza (Katalogis, 2016)
In the budget year of 2013-2015, the absorption of local government budgets in Palu City shows accumulation in the past three months. This condition can cause the loss of value for money in the governmental budget (BPKP, 2012). Performance-based budgeting can foster effective programs with an efficient use of funds to achieve the organizational goals (Young, 2003). Performance-based budgeting is designed to increase good governance such as transparency and accountability in making the decisions for resource allocation (Vian, 2013). Accountability will increase the responsibility of public officials in carrying out their duties based on the procedure in order to minimize inefficiency that leads to high cost and slowness of public services (Mardiasmo, 2009). This research applies quantitative approach with sample of 41 governmental units that selected through purposive sampling method. Data is analyzed with SEM-PLS method. The result show that: 1) the implementation of performance-based budgeting has a positive but insignificant influence on value for money performance; 2) performance-based budgeting has a positive and significant influence on good governance; 3) the application of good governance has a positive and significant influence on value for money performance; and 4) the implementation of performance-based budgeting has an indirect influence on value for money performance through good governance.Â